1.0k views
4 votes
What is wrong with this solution? -6t + 16 = -8 Step One: -6t + 16 = -8 - 16 Step Two: -6 • -6t = -24 • -6 Solution: t = 144

User BaCaRoZzo
by
4.8k points

2 Answers

3 votes
I think this should be it?
What is wrong with this solution? -6t + 16 = -8 Step One: -6t + 16 = -8 - 16 Step-example-1
User BSeitkazin
by
4.9k points
2 votes

Answer:

t = 4

Explanation:

In step two, instead of multiplying by -6 on both sides, you need to divide by -6 to isolate t.

-6t = -24

÷-6 ÷-6

t = 4

When you multiply by -6 on both sides, the equation would be 36t = 144, which is not what we want. The opposite of multiplication is division, and in order to get the answer, you divide by the number multiplied.

User Nils Wasell
by
4.7k points